ANALISIS PEMBELAJARAN SECARA SINKRON DAN ASIKRON PADA PEMBELAJARAN DIGITAL - Haekal febriansyah; Muhammad Yahya; Abdul Muis Mapalotteng (UNM Journal of Technology and Vocational, 2022)
The purpose of thisstudy isto collect, process, and describe data regarding (1) The level of effectiveness of synchronous and asynchronous learning on postgraduate students during the digital learning era (2) The level of satisfaction of postgraduate students with synchronous and asynchronous learning during the digital learning era (3) Combination of synchronous and asynchronous learning in one course according to postgraduate students. The type of research conducted is descriptive qualitative research. The population of this study were postgraduate students from Makassar State University and the University of Indonesia with probability sampling technique using simple random sampling method. The results of this study indicate that the average value of the effectiveness of synchronous learning forpostgraduate students is 4 out of 5 and asynchronous learning is 3.70 out of 5 while the average value of postgraduate student satisfaction for synchronous learning is 3.94 out of 5 and for asynchronous learning is 3.76 out of 5, and all interview respondents agreed that synchronous and asynchronous learning can be combined in one course.